Exclusive Breast Milk and Additional Milk For The Nutritional Status of Children Aged 12-23 Months in Limo District, Depok City - Tampubolon, Elmina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Stunting is the result of chronic or recurrent malnutrition and often lasts a lifetime. Stunting can be caused by a lack of awareness of mothers in the practice of feeding children. The purpose of this study was to determine the relationship between exclusive breastfeeding and supplementary milk with the nutritional status of children. The research hypothesis is that there is a relationship between exclusive breastfeeding and supplementary milk with the nutritional status of children. The research took place in Limo District, Depok City. The research design was a case-control study. The subjects in this study were children aged 12-23 months. Cases are stunted children aged 12-23 months with a PB/U index with a z score of -3 SD to less than -2 SD, while controls are children with normal nutritional status or who have a PB/U index with a z score of -2 SD to + 3 SD. Based on the sampling formula, a minimum sample of 50 was obtained. The final number of samples was 110 children. Data analysis was carried out univariate, bivariate and multivariate with multiple logistic regression. The results of the analysis showed that there was a relationship between supplementary milk feeding and the frequency of feeding with the nutritional status of the child, while exclusive breastfeeding was not associated with the child's nutritional status. Thus, supplemental feeding and frequency of feeding are related to the nutritional status of children. From these results, the researchers recommend that health workers need to strengthen their educational programs to the community, related to parenting, feeding and clean living patterns so that children's growth and development are optimal.Stunting merupakan hasil dari kekurangan gizi kronis atau berulang dan sering berlangsung seumur hidup. Stunting dapat disebabkan oleh kurangnya kesadaran ibu dalam praktik pemberian makanan pada anak. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara pemberian ASI Eksklusif dan susu tambahan dengan status gizi anak. Hipotesis penelitian adalah ada hubungan antara pemberian ASI Eksklusif dan susu tambahan dengan status gizi anak Penelitian berlangsung di Kecamatan Limo, Kota Depok. Desain penelitian adalah studi kasus kontrol. Subyek pada penelitian ini adalah anak usia 12-23 bulan. Kasus adalah anak stunting usia 12-23 bulan dengan indeks PB/U dengan z score -3 SD sd kurang dari -2 SD, sedangkan kontrol adalah anak dengan status gizi  normal atau yang memiliki indeks PB/U dengan z score -2 SD sd + 3SD. Berdasarkanrumuspengambilansampeldiperolehsampel minimal sebanyak 50.Jumlahakhirsampeladalah 110 anak. Analisis data dilakukan secara univariat, bivariat dan multivariat dengan regresi logistik berganda Hasil analisis menunjukkan bahwa ada hubungan antara pemberian susu tambahan dan frekuensi pemberian makan dengan status gizi anak, sedangkan pemberian ASI Eksklusif tidak berhubungan dengan status gizi anak. Dengan demikian Pemberian susu tambahan dan frekuensi pemberian makan berhubungan dengan status gizi anak. Dari hasil tersebut maka peneliti merekomendasikan bahwa Tenaga kesehatan perlu menguatkan program edukasinya kepada masyarakat, terkait pola asuh, pemberian makan dan pola hidup bersih sehingga pertumbuhan dan perkembangan anak optimal.